Pattern of Malocclusion in Orthodontic Patients in South-Eastern Region of Nepal - Acharya, Anand; Bhattarai, Bhushan; George, Diana; Bhagat, Tarakant (Orthodontic Journal of Nepal, 2017)
Introduction: Occlusal traits in orthodontic patients have been studied in different parts of Nepal. However, very few data are available on malocclusion in south-eastern region of Nepal. Objective: To assess the pattern of malocclusion occurring in orthodontic patients in south-eastern region of Nepal, and to estimate the age of presentation of Class II malocclusion among the patients. Materials & Method: Data were collected from 150 pre-treatment study models and lateral cephalograms from two orthodontic specialty clinics in Biratnagar. Angle’s classification system was used to determine dental malocclusion and ANB angle was used to determine skeletal malocclusion. Chi square test was used to test the association between dental and skeleton malocclusions. Result: Angle’s Class I malocclusion was found in 95(63.33%), Class II Div 1 in 41(27.33%), Class II Div 2 in 13(8.66%) and Class III in 1(0.66%). Among all subjects; 119 (79.33%) had skeletal Class I, 24(16%) had skeletal Class II and 7(4.66%) had skeletal Class III. There was significant association between dental and skeletal malocclusions. The average age for reporting Class II Div 1 malocclusion was 16.5 years and Class II Div 2 malocclusion was 19 years. Conclusion: Angle’s Class I is the most common malocclusion followed by Class II and Class III among orthodontic patients in south-eastern Nepal. The subjects lack awareness on age factor for orthodontic treatment.